¿Visibilizar y/o activar? Notas para la gestión de una Casa de la Cultura - Suárez Trejo, Javier (2018)
A house is a space that we inhabit. However, a house also teaches us to inhabit (it) offering multiple ways to live in it with human beings, people and objects, that are important to us. In other words, a house activates multiple ways to inhabit it so that it and we transform that shared space in where we live: the country, for example. Having this in mind, what is a house of culture? Does it make sense today? To answer these questions, the following article is divided into two sections. The first section focuses on the pedagogical function of the House of Culture, according to José María Arguedas, who was its first director between 1963 and 1964. For Arguedas, the house had a dual function, «adapter» and «creative», which responded to the urgent needs of the migrants in the city of Lima. The second section describes and analyzes the functions of the House of Peruvian Literature, active since 2009, and suggests the need to challenge and transform those functions that seems to follow a visibilizing and not pedagogical notion of literature. throughout the article, useful distinctions to rethink cultural management and policies.